Impact of Technological Intervention on Rabi Pulses for Enhancing Income and Nutritional Security (Indian Journal of Extension Education, 2018)
Uttar Pradesh is the second largest producer of pulses in the country accounting about 16 per cent of the total production. The area, production and productivity of rabi pulses in Uttar Pradesh and the district Bhadohi of U. P. is quite low as compared to other state due to poor crop productivity, lack of awareness of suitable protection and post harvest technologies. Krishi Vigyan Kendra, Bhadohi was conducted front line demonstrations on improved technologies of Rabi pulses i.e. field pea, chickpea and lentil at farmers field during 2010-11 to 2014-15 with the objectives of, to exhibit the performance of recommended high yielding varieties of Rabi pulses and to collect feedback information for further improvement. A total of 387 demonstrations of rabi pulses were conducted in fifty villages encompassing an area of 26.81 hectares. The results of rabi pulses over a span of five years revealed that the average yield of field pea (23.3q/ha.), chickpea (21.7q/ha.) and lentil (6.13q/ha.) were obtained under demonstration plot and per cent increase in yield was 27.29, 34.73 and 34.71 per cent more against the farmer practice, respectively. Due to proven technological interventions average net profit return was recorded 31727.00, 43992.00 and 19422.00 per hectare in field pea, chickpea and lentil, respectively. The outcome of the demonstration inspired the farming communities to replace their old varieties with high yielding resistant varieties to biotic and abiotic stresses. In addition improved package of practices of cultivation are being followed by the pulse growers and achieved more return per unit area.